Phylogenetic Analysis of UreABC Protein in Ureolytic Bacteria as Self-Healing Agent in Concrete - Amalia Danti Safa Audia; Else Vilia Setiawan; Giral Baines Mora; Grace Christy; Nabila Shafa Yumna Salsabila; Firda Nuri Asyhari; Turhadi Turhadi; Fatchiyah Fatchiyah (JSMARTech, 2023)
Concrete is one of Indonesia's most widely used materials in infrastructure development because it is strong enough to withstand pressure, adaptable, and has relatively low maintenance costs. Bacteria are potential agents that can be used to close cracks in concrete. Therefore, this research is aimed to determine which bacteria can produce the enzyme urease based on constructing a phylogenetic tree, the ability to produce spores, and the characteristics of ureolytic bacteria. This study used four sequences of ureolytic bacteria that code for ureABC, namely Bacillus, Clostridium, Pseudomonas, and Enterobacter, with Micrococcus terreus as the outgroup. The four bacterial groups with outgroups were aligned and phylogeny constructed using the Neighbor-Joining (NJ) method with 1000 replication and grouped based on genetic distance in MEGA-X software. Then further screening was carried out based on the ability to form endospores and the characteristics of ureolytic bacteria. Phylogenetic analysis shows that the bacterial groups Bacillus, Enterobacter, Clostridium and Pseudomonas have a fairly close kinship, the construction is based on proteins, genus, cell shape, gram characteristics, and habitat. The ureolytic bacteria group predicted to have the highest potential as a biomaterial agent comes from Bacillus sp. and Clostridium sp. due to its ability to form endospores. Ureolytic activity is indicated by an increased pH value and urea degradation activity due to ammonification with Bacillus sp. having a pH of 6.0-8.0. In contrast, the pH value of Clostridium sp. is unknown because further research is needed in vitro.